Concomitant Fracture Radial Head and Shaft With Dislocation of the Distal Radioulnar Joint: A Rare Variant of the Essex-Lopresti Lesion. (8th August 2022) - Kaul, Rajiv; Sood, Chetan; Akhoon, Neha
Abstract : The Essex-Lopresti lesion is a challenging injury both for diagnosis and management. These often tend to be missed, resulting in incapacitating pain and joint stiffness despite treatment. In rare circumstances, they may occur in association with other injuries of the forearm or elbow. We describe an atypical Essex-Lopresti variant comprising a radial head and shaft fracture with an associated distal radioulnar joint dislocation in a 36-year-old man.